UJI AKTIVITAS ANTIBAKTERI DAUN RAMBAI (Baccaurea motleyana Mull. Arg.) - Rachman, Ferry Aditya; Saleh, Chairul; Marliana, Eva (JURNAL ATOMIK, 2020)
Antibacterial activity of methanol extract, n-hexane fraction, ethyl acetate and residue of methanol of rambai (Baccaurea motleyana Mull. Arg.) leaves have been done. The extraction process with maceration of the rambai (B. motleyana Mull. Arg.) leaves using a methanol solvent, then proceed with fractionation using the liquid-liquid partition method to obtain the n-hexane, ethyl acetate and residual methanol fractions. Based on the results of phytochemical screening of secondary metabolites contained in the total methanol extract contains triterpenoid, steroid, phenolic and flavonoid compounds. The n-hexane fraction contains flavonoid and steroid compounds, whereas the ethyl acetate contains flavonoid and phenolic, and residual methanol fractions contains flavonoid, phenolic and triterpenoid compounds. Based on the results of the antibacterial activity test on the bacteria Propionibacterium acnes and Escherichia coli, the values ​​of methanol extract, ethyl acetate fraction and the residue of methanol fraction of the leaves B. motleyana Mull. Arg. for Propionibacterium acnes has a MIC value of 4% and Escherichia coli bacteria at 8%. From the results of the antibacterial activity test it can be concluded that the methanol extract, ethyl acetate and residue of methanol fraction have antibacterial activity against the Propionibacterium acnes KCCM 41747 and Escherichia coli ATCC 25922.